Outlining the past of the Hungarian goose breeding - Kozák, János (Animal welfare, Ethology and Housing Systems (AWETH), 2021)
This paper outlines briefly the goose keeping and goose breeding having been formed in the area of Hungary. In the history of Magyars the goose has become an essential domestic animal of the Hungarian settlements already from the beginning. The extensive agricultural production has offered favourable conditions for goose keeping. As a consequence of the transformation of the agriculture, ravages of war, than the socialist large-scale farming the goose stock has gradually diminished however. As a result of production incentives the slaughter goose production started to increase as of the 1960s years. The product range of slaughter products has enlarged beside the fattened goose with meat-type goose, broiler goose, heavy meat and oat reared goose. The breed assortment has been transformed: meat- and liver type genotypes have spread. Hungary has became one of the three biggest goose meat production, the leading country of foie grass production as well as second in the rank of goose feather producing and distributor countries after Chine in the end 1970s. The Hungarian goose keeping and manufacturing of goose products have been implemented according to the animal welfare regulations, and legal rules from the beginning of the 19th century.